Variation Order (Change Order) in Oil & Gas Projects - Al Hammadi, Ahmed Salem (2009)
This thesis presents result of a study on causes and effects of variation order (change order) in Oil & Gas projects in the UAE. To achieve the study objective the researcher carried a literature review of the subject covering periodicals, dissertations, previous research studies and books written on the subject of variation orders (change orders). In light of the literature study the researcher developed survey questionnaires. The questionnaire was designed to meet the research aims and objectives and to test its hypothesis. The aim of the questionnaire is to identify the most important causes of variation order in oil and Gas projects; however, it was also valuable to examine the ground that may cause these variations, including procurement methods and tendering arrangements. In addition, it was expected that the respondents' knowledge and experience would differ from one to another, and that this might have an impact on their answers, so attention was paid to addressing this point. A list of such ideas was considered in constructing the questionnaire In order to present the questionnaire in a systematic way, it was decided to divide the questions into four sections: Section One – questions concerned with person experience. This contains general questions about the profession, period of experience, sector and size of projects. Section Two – questions dealing with contractual arrangement, including procurement methods and tendering arrangement. Section Three – questions dealing with performance of the projects that the person has been involved in. This section identifies the number of projects that the person has participated in and then and then asks how many of them were varied and what the average variation in term of cost. It also has a question about the average variation that was authorized by client, the party responsible for the variation and five most important causes of variation. Section Four – this section includes the list of 67 causes of variation order in Oil and Gas Projects. Four scales were identified to calculate the frequency and occurrence and the degree of severity of each cause. Responses from 43 clients, consultants and contracts working in the field of oil & gas projects were analysed. Analysis of data indicated that the cost overruns due to variation orders (change orders) were less that 10% of the original contract value. The study also concludes that the project management consultant (PMC) and client make an integrated team with the client in order to review the design as one team to understand the design and to ensure owner's needs and expectations.